ANALISIS FAKTOR YANG MEMPENGARUHI LOYALITAS KONSUMEN DI PT. KEBAKKRAMAT ELANG PERKASA - Puji Tri Setyowati; Ida Ayu Kade R K (Universitas Bina Taruna Gorontalo, 2022)
This study aims to analyze the factors that influence consumer loyalty at PT. Kebakkramat Elang Perkasa. The method of data collection was carried out using a questionnaire containing questions related to the research variables and using a simple random sampling technique. The collected data is then processed and tabulated using the data instrument test, classical assumption test, F test, coefficient of determination test, multiple linear regression analysis, and t test. The results of the analysis show that the variables of marketing strategy, product quality, service quality, and customer satisfaction each have a significant positive effect on consumer loyalty.